Metabolite profiling and adaptation mechanisms of Aspergillus cristatus under pH stress - Zhang, Rongrong; Zhou, Lihong; Xie, Luyi; Lu, Lingqing; Zhou, Hang; Yang, Yi; Hu, Jiuping (Frontiers in Microbiology, 2025)
IntroductionpH is an important environmental factor affecting the survival of fungi, and Aspergillus cristatus, which can grow and reproduce over a wide range of pH, is suitable for studying their adaptation mechanism to pH stress.MethodsIn this study, A. cristatus was cultured on plates of different initial pH (pH 3.8-8.0), with the results revealing distinct morphologies at pH 3.0–5.0, pH 6.0–7.0 and pH 8.0. Liquid chromatography-mass spectrometry (LC-MS) and multivariate analysis subsequently were used to analyze the changes of substance metabolism of A. cristatus at different pH.Results and discussionLC-MS and multivariate analyses showed that A. cristatus’s growth at different pH involved significantly different metabolites. In particular, comparing pH 4.0 vs pH 6.0, pH 6.0 vs pH 8.0 and pH 4.0 vs pH 8.0 revealed a total of 317, 171 and 404 significantly different substances, respectively. Finally, as the pH changed from 4.0 to 6.0 to 8.0, eight changes in the patterns of differential substances were identified. At low pH, A. cristatus accumulated large amounts of energy substances (e.g., adenosine), active antioxidants (e.g., glutathione) and osmo-protective substances (e.g., raffinose). In contrast, at high pH, large amounts of phosphatidylcholine (PC), lysophosphatidyl ethanolamine (LPE), lysophosphatidyl choline (LPC), lysophosphatidyl serine (LPS) related to biofilms were synthesized, alongside antioxidants (e.g., formononetin) and acidic substances. The aforementioned results indicate that A. cristatus adapts to changes in pH by adjusting their metabolite synthesis. Therefore, under unsuitable pH environments, A. cristatus synthesizes specific sets of metabolites that play key roles to cope with the stress.